Study of the differential response to zinc of prostate cell spheroids using the synchrotron radiation X‐ray microfluorescence technique. (19th March 2015) - Leitão, R. G.; Santos, C. A. N.; Palumbo, A.; Souza, P. V. R.; Canellas, C. G. L.; Anjos, M. J.; Nasciutti, L. E.; Lopes, R. T.
<x xml:space="preserve">Abstract</x> X‐ray microfluorescence imaging technique has very often been used as a significant tool in biomedical research to obtain information regarding the distribution of elements in tissue and cell samples. This study investigated Zn distribution in benign prostate hyperplasia (BPH) and prostate cancer (DU145) cell spheroids and analyzed the different response to Zinc treatment using synchrotron X‐ray microfluorescence (μSRXRF). The μSRXRF measurements were performed at the XRF beam line at the Synchrotron Light National Laboratory (Campinas, Brazil). The results showed non‐uniform distribution of Zn in all the spheroids analyzed. The differential response of DU145 and BPH cell spheroids to zinc suggests that there are different mechanisms of Zn accumulation in tumor cells. Copyright © 2015 John Wiley & Sons, Ltd.